IMPLEMENTASI BANTUAN LANGSUNG TUNAI (BLT) DANA DESA DALAM MENANGANI DAMPAK COVID-19 (STUDI KASUS DESA MEKAR SARI KECAMATAN GUNUGSARI KABUPATEN LOMBOK BARAT) - ISMI ARIFIANA RAHMANDARI; SANDI JUSTITIA PUTRA; SAPOAN SAPOAN (Universitas Mahasaraswati K. Mataram, 2023)
This research discusses the implementation of direct cash assistance from village funds for communities affected by Covid-19 in Mekarsar Village, Gunungsari District, West Lombok, bearing in mind that the impact of Covid-19 is very devastating, especially for the community's economy, not only Indonesian people but the whole world feels the impact. .So in this case the researcher tries to dig deeper into the Village Fund Direct Cash Assistance (BLT) DD, related to what obstacles, barriers and challenges exist so that we don't always blame the government and we always feel that we are in the right. to find out how the Village Fund Direct Cash Assistance (BLT-Village Fund) is implemented and the impact of implementing Village Fund Direct Cash Assistance (BLT-Village Fund). Theoretically, the benefits of this research are expected to be able to provide an overview of the Implementation of Direct Village Fund Cash Assistance (Village Fund BLT) in Mekarsari Village, Gunungsari District, West Lombok. The research method used is a qualitative method with a case study approach. The results of the research show that there are still many obstacles and challenges that occur, including: Many family members in the community are poor. as well as existing budget limitations so that we are forced to reduce beneficiary families.